2012
DOI: 10.1038/nsmb.2348
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structures of the JAK2 pseudokinase domain and the pathogenic mutant V617F

Abstract: The protein tyrosine kinase Jak2 mediates signaling through numerous cytokine receptors. Jak2 possesses a pseudokinase domain (JH2) and a tyrosine kinase domain (JH1). Through unknown mechanisms, JH2 regulates the catalytic activity of JH1, and hyperactivating mutations in the JH2 region of human Jak2 are causative for myeloproliferative neoplasms (MPNs). We showed previously that Jak2 JH2 is in fact catalytically active. Here, we present crystal structures of human Jak2 JH2, both wild-type and the most preval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
247
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 208 publications
(257 citation statements)
references
References 48 publications
8
247
0
2
Order By: Relevance
“…Secondary structure analysis of αC showed that the time αC residues (587-602) were in an α-helical conformation increased upon ATP binding from 41% to 65% in wild type and from 73% to 84% in V617F (Fig. S6D) (16). Taken together, these data imply a stabilizing effect for ATP binding on JH2 and a difference in the αC region of ATP-bound JAK2 JH2 V617F compared with wild type.…”
Section: Molecular Dynamic Simulations Imply a Stabilizing Effect Forsupporting
confidence: 62%
See 4 more Smart Citations
“…Secondary structure analysis of αC showed that the time αC residues (587-602) were in an α-helical conformation increased upon ATP binding from 41% to 65% in wild type and from 73% to 84% in V617F (Fig. S6D) (16). Taken together, these data imply a stabilizing effect for ATP binding on JH2 and a difference in the αC region of ATP-bound JAK2 JH2 V617F compared with wild type.…”
Section: Molecular Dynamic Simulations Imply a Stabilizing Effect Forsupporting
confidence: 62%
“…The crystal structure of JAK2 JH2 V617F is highly similar to the wild-type structure (16), with small changes in αC and the β3-αC linker and a slight change in the topography of the ATP binding pocket due to alignment of Phe617, Phe595, and Phe594 (the latter two in αC) in V617F (Fig. S1).…”
Section: Resultsmentioning
confidence: 83%
See 3 more Smart Citations